PENGARUH MENTORING SEBAGAI PERSUASI SOSIAL TERHADAP KEPERCAYAAN DIRI MAHASISWA TINGKAT AKHIR DI MASA ENDEMI - Rahadatul 'Aisyh Khalda Noor Hamzah (2023)
Communication is the most important thing between students and lecturers during thesis guidance, but the impact of the pandemic has an effect that reduces the intensity of lecturers with students during guidance.This study aims to discuss the effect of mentoring in social persuasion on the self- onfidence of final semester students of communication science students in the 2018 academic year at UPN Veteran Jakarta using self-efficacy theory which is linked to persuasive communication in social persuasion. The method used in this research is the method and type of explanatory research using primary data sources and secondary data. The sampling technique was carried out by simple random sampling technique. Researchers used data analysis techniques ranging from validity testing, reliability testing, correlation testing, linear regression testing and hypothesis testing to find out the results of the study. The final results of this study indicate that there is a positive and significant influence between mentoring variables and self-confidence. Based on the results of the simple linear regression calculation test, the researcher obtained a value of 0.867. This value proves that there is a very strong influence. These results indicate that mentoring has a very strong influence on the selfconfidence of final year students of communication science students in the 2018 academic year at UPN Veteran Jakarta. So it can be concluded that there is a significant (real) effect between mentoring and self-confidence. Students feel that the direction or instructions from the lecturer is the most important thing for students because it affects their obligation to complete the final task as the student's responsibility.